2017
DOI: 10.1063/1.4983159
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced annealing stability and perpendicular magnetic anisotropy in perpendicular magnetic tunnel junctions using W layer

Abstract: The magnetic properties of the perpendicular storage electrode (buffer/MgO/FeCoB/Cap) were studied as a function of annealing temperature by replacing Ta with W and W/Ta cap layers with variable thicknesses. W in the cap boosts up the annealing stability and increases the effective perpendicular anisotropy by 30% compared to the Ta cap. Correspondingly, an increase in the FeCoB critical thickness characterizing the transition from perpendicular to in-plane anisotropy was observed. Thicker W layer in the W(t)/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…[12][13][14] However, a cap layer used on top of storage layer, can also indirectly influence the magnetic and transport properties of the pMTJ by modifying the interfacial and bulk physicochemical and electronic properties. [15][16][17][18] The main physicochemical modifications are Boron absorption from the storage layer 17 or interdiffusion during sputtering or post deposition anneals. 15 In an earlier paper, we reported significant improvement of annealing tolerance using thick W/Ta cap as compared to Ta because of structural stiffening of the stack and much weaker interdiffusion with W than with Ta.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] However, a cap layer used on top of storage layer, can also indirectly influence the magnetic and transport properties of the pMTJ by modifying the interfacial and bulk physicochemical and electronic properties. [15][16][17][18] The main physicochemical modifications are Boron absorption from the storage layer 17 or interdiffusion during sputtering or post deposition anneals. 15 In an earlier paper, we reported significant improvement of annealing tolerance using thick W/Ta cap as compared to Ta because of structural stiffening of the stack and much weaker interdiffusion with W than with Ta.…”
mentioning
confidence: 99%
“…13,14 As a consequence, the effective magnetic critical thicknesses (tc), listed in antiferromagnetically coupled by 0.9 nm Ru layer. 16,21 Co/Pt MLs based SAF are widely used in the pMTJ stacks 22,23 because of their large PMA [24][25][26] , which makes them good candidates for realizing magnetically hard layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results demonstrated that after annealing at 420 °C for 10 min, the p‐MTJ showed a high TMR ratio of 138% and the resistance area product (RA) of 0.5 MΩ µm 2 . Subsequently, Chatterjee et al reported that after annealing at 425 °C, the p‐MTJ with W(2 nm)/Ta(1 nm) capping layer exhibited a TMR ratio of 117% and the low RA of 8 Ω µm 2 , which can be attributed to the thin MgO layer …”
Section: Modulation Of Hm/fm Interface For High Tmrmentioning
confidence: 99%
“…In the double CoFeB-MgO interface structure, a thin metal layer such as Ta, W, or Mo was inserted to absorb boron from the CoFeB layers (MgO/CoFeB/insertion layer/CoFeB/MgO) for high tunnel magnetoresistance (TMR) ratio and perpendicular anisotropy [15,16,29,[33][34][35][36][37][38][39][40][41][42][43][44]. First, Ta was used as insertion material because Ta has a bcc crystal structure and is a good boron absorber, as mentioned above.…”
Section: (1) High Thermal Tolerance By Controlling Boron Composition mentioning
confidence: 99%